SEMANTIC STRUCTURE OF THE CONCEPT LIFE / ÓMIR IN ENGLISH AND KARAKALPAK LANGUAGES - Djabbarbergenova, Miyirxan Maksetbayevna (SCIENCE and SOCIETY, 2026)
In cognitive linguistics, the notion of a concept is central to understanding how language reflects and shapes human thought, which can be defined as a mental unit of knowledge that structures human experience and provides the basis for linguistic meaning. The given article aims to examine the semantic structure of the concept LIFE / ÓMIR in English and Karakalpak languages within cognitive linguistics exploring how this concept is structured through different semantic dimensions and how these structures vary across cultures.